Comparative study on energy extraction from vibrating square cylinder - Mohd. Maruai, Nurshafinaz (2015)
In this paper, the prospect of harvesting energy from flow induced-vibration of a square cylinder is assessed. The extraction of energy from the flow is attained by mounting the square cylinder on a one-degree elastic system with a mass-damping (m*ζ) of 2.75. OpenFOAM®, an open source CFD package is used to model the flow induced motion of the square cylinder. A theoretical formulation to estimate the lift force acting on the square cylinder is derived to confirm the results obtained by the simulation. A good agreement between the results is obtained. The amplitude vibration and lift force are then used to estimate the power induced by the oscillating square cylinder. Energy in the micro scale range can be harvested from this flow induced-vibration system. This type of alternative green energy is suitable for the micro energy harvester system required for sensors in many engineering structure for health monitoring purpose.